Thermophysical performances of (La1/6Nd1/6Yb1/6Y1/6Sm1/6Lu1/6)2Ce2O7 high-entropy ceramics for thermal barrier coating applications. Issue 2 (15th January 2022) - Zhang, Hongsong; Zhao, Liming; Sang, Weiwei; Chen, Xiaoge; Tang, An; Zhang, Haoming
Abstract: In this study, a novel high-entropy oxide of (La1/6 Nd1/6 Yb1/6 Y1/6 Sm1/6 Lu1/6 )2 Ce2 O7 was prepared using a sol–gel and high-temperature sintering technology. Additionally, its lattice structure, micro-morphology, elemental composition, and thermophysical and mechanical properties were evaluated. The results revealed that the obtained oxide powder has a typical fluorite-type lattice with particle sizes in the range of∼30–100 nm. The bulk sample has a dense microstructure and uniform elemental distribution. Owing to its low lattice order, the thermal expansion coefficient of (La1/6 Nd1/6 Yb1/6 Y1/6 Sm1/6 Lu1/6 )2 Ce2 O7 is greater than that of Sm2 Ce2 O7, which also exhibits excellent lattice stability up to 1200 °C. Further, owing to phonon scattering due to lattice distortion, oxygen vacancy, and cation substitution, the thermal conductivity of (La1/6 Nd1/6 Yb1/6 Y1/6 Sm1/6 Lu1/6 )2 Ce2 O7 is lower than that of Sm2 Ce2 O7, while its mechanical performance is inferior to that of 7YSZ.